2018
DOI: 10.2147/idr.s170233
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-resistant <em>Acinetobacter baumannii</em> and <em>Pseudomonas aeruginosa</em>: characterization of carbapenemase genes and E-test evaluation of colistin-based combinations

Abstract: BackgroundCarbapenamase producing Acinetobacter baumannii and Pseudomonas aeruginosa are emerging worldwide limiting the use of carbapenems as effective and safe drugs.PurposeTo characterize different carbapenemase genes carried by carbapenem-resistant (CR) A. baumannii and P. aeruginosa isolates and to evaluate the in vitro effect of some colistin-based combinations by E-test method in Zagazig University Hospitals ICU isolates.MethodsCR A. baumannii and P. aeruginosa isolated from the surgical intensive care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 38 publications
6
30
3
Order By: Relevance
“…On the other hand, our findings were different from another study that was conducted in Zagazig hospital in Egypt, which reported that blaOXA-23 was the most prevalent (90%) followed by, blaNDM (66.7%) then blaGES (50%) in CR A. baumannii , respectively. 38 However, genes coding for blaVIM, blaGES, blaNDM and blaIMP were identified in 50%, 40.9%, 27.3% and 18.2% of CR P. aeruginosa , respectively. 38 The difference between the respective study and our study could be attributed to other factors such as geographical and patient factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our findings were different from another study that was conducted in Zagazig hospital in Egypt, which reported that blaOXA-23 was the most prevalent (90%) followed by, blaNDM (66.7%) then blaGES (50%) in CR A. baumannii , respectively. 38 However, genes coding for blaVIM, blaGES, blaNDM and blaIMP were identified in 50%, 40.9%, 27.3% and 18.2% of CR P. aeruginosa , respectively. 38 The difference between the respective study and our study could be attributed to other factors such as geographical and patient factors.…”
Section: Discussionmentioning
confidence: 99%
“… 38 However, genes coding for blaVIM, blaGES, blaNDM and blaIMP were identified in 50%, 40.9%, 27.3% and 18.2% of CR P. aeruginosa , respectively. 38 The difference between the respective study and our study could be attributed to other factors such as geographical and patient factors.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies reveal that bacteria can acquire antibiotic resistance in the existence of drug efflux pumps; new findings indicate that these systems, by removing various compounds, contribute to bacteria that has had time to acquire resistance to the various classes of antibiotics, including β-lactams, tetracyclines, aminoglycosides, cephalosporins and fluoroquinolones [21], [27]. MDR and XDR strains have been recognized as a major concern in different hospital areas, particularly the intensive care unit [18], [19], [28]. According to US Food and Drug Administration–published guidelines as well as the results of previous studies, a few antibiotics such as tigecycline, minocycline and colistin can be used for the treatment of MDR A. baumannii [12], [13], but tigecycline resistance is increasingly being reported [16].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, the United States CDC declared that carbapenem-resistant Enterobacteriaceae (CRE), 4) as well as drug-resistant Neisseria gonorrhoeae and Clostridium difficile are an urgent threat to public health. 5) Furthermore, WHO recently published its "priority list of antibiotic-resistant bacteria for R&D." 6) This list classified carbapenem-resistant Acinetobacter baumannii, carbapenem-resistant Pseudomonas aeruginosa, 7) and carbapenem-resistant extended spectrum β-lactamase (ESBL)-producing Enterobacteriaceae as "Priority 1: critical." 8,9) This list demonstrates that the development of antibiotics active against MDR Gram-negative bacteria, particularly carbapenemaseproducing organisms, is key to preventing future catastrophic pandemic outbreaks.…”
Section: Introductionmentioning
confidence: 99%